2020
DOI: 10.1103/physrevb.101.045129
|View full text |Cite
|
Sign up to set email alerts
|

Strongly coupled electron liquid: Ab initio path integral Monte Carlo simulations and dielectric theories

Abstract: The strongly coupled electron liquid provides a unique opportunity to study the complex interplay of strong coupling with quantum degeneracy effects and thermal excitations. To this end, we carry out extensive ab initio path integral Monte Carlo (PIMC) simulations to compute the static structure factor, interaction energy, density response function, and the corresponding static local field correction in the range of 20 ≤ rs ≤ 100 and 0.5 ≤ θ ≤ 4. We subsequently compare these data to several dielectric approxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 106 publications
(203 reference statements)
9
93
0
Order By: Relevance
“…In the HED regime, both dielectric methods provide accurate results with a maximum deviation in χ(q) of ∼ 4% (∼ 1%) for RPA (STLS) at θ = 0.85 and r s = 0.5. In this way, we have bridged the gap between previous PIMC simulation results in the WDM regime and beyond [75,11,76] and perturbative expansions like dielectric theories [3,130,131]; iii) we have shown that our PIMC approach to the static density response converges towards RPA both for high temperatures and densities, and is in striking agreement to highly accurate CPIMC data, where they are available. This illustrates the consistency of our approach, and further corroborates our current understanding of the UEG at finite temperature.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In the HED regime, both dielectric methods provide accurate results with a maximum deviation in χ(q) of ∼ 4% (∼ 1%) for RPA (STLS) at θ = 0.85 and r s = 0.5. In this way, we have bridged the gap between previous PIMC simulation results in the WDM regime and beyond [75,11,76] and perturbative expansions like dielectric theories [3,130,131]; iii) we have shown that our PIMC approach to the static density response converges towards RPA both for high temperatures and densities, and is in striking agreement to highly accurate CPIMC data, where they are available. This illustrates the consistency of our approach, and further corroborates our current understanding of the UEG at finite temperature.…”
Section: Discussionsupporting
confidence: 73%
“…Shortly thereafter, two of us [76] have extended these efforts to even stronger coupling strength, 20 ≤ r s ≤ 100 (blue diamonds), where the UEG forms an electron Figure 1. Parameter overview of quantum Monte Carlo data for the static density response of the uniform electron gas in the r s -θ plane.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, addressing this issue would require a modification of the corresponding Padé approximation to automatically fulfill some additional constraints. ii) the current validity domain of, e.g., the GDSMFBB parametrization to 0 ≤ r s ≤ 20 can be significantly extended by incorporating the recent ab initio PIMC results for the electron liquid regime (20 ≤ r s ≤ 100) by Dornheim et al [128]. iii) new ab intio QMC results at low temperature, θ ∼ 10 −1 , could help to more accurately resolve open thermodynamic questions like the effective mass enhancement [129], but are difficult to obtain due to the notorious fermion sign problem [130].…”
Section: A Summary Of Ab Initio Static Resultsmentioning
confidence: 99%